2003
DOI: 10.1143/jjap.42.4406
|View full text |Cite
|
Sign up to set email alerts
|

Fast Optical Recording of Polarization Holographic Grating Based on an Azo-Dye-Doped Polymer-Ball-Type Polymer-Dispersed Liquid Crystal Film

Abstract: Gallium phosphide (GaP) nanoparticles were synthesized by reacting GaCl 3 with Na 3 P in xylene. An electron spin resonance spectrum attributed to the Ga self-interstitial (Ga i ) defect in GaP nanoparticles was observed with factor g = 2.0028. From the ultraviolet and visible (UV-vis) spectrum it is inferred that GaP nanoparticles exhibit a direct transition and an indirect transition, and the blue-shifted band gaps are ascribed to the Ga i defect as well as the nanosize effect. In the Raman spectrum the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…which describes the polarization state of an electromagnetic wave with electric field components along the x and y axes and The polarization state of light can be determined from interferometric and holographic measurements [13] or using space-variant subwavelength metal-stripe polarizers [14] in the spatial Fourier-transform polarimetry technique. Light polarization is essential in determining the dielectric constant of materials using ellipsometry [15], in polarization-sensitive optical coherence tomography [16], especially suited for examining biological samples, and in designing advanced devices such as polarization holographic gratings for fast optical recordings [17] and polarization-bistable lasers for optical memory [18].…”
Section: Optical Analog Of Ballistic Charge Carriersmentioning
confidence: 99%
“…which describes the polarization state of an electromagnetic wave with electric field components along the x and y axes and The polarization state of light can be determined from interferometric and holographic measurements [13] or using space-variant subwavelength metal-stripe polarizers [14] in the spatial Fourier-transform polarimetry technique. Light polarization is essential in determining the dielectric constant of materials using ellipsometry [15], in polarization-sensitive optical coherence tomography [16], especially suited for examining biological samples, and in designing advanced devices such as polarization holographic gratings for fast optical recordings [17] and polarization-bistable lasers for optical memory [18].…”
Section: Optical Analog Of Ballistic Charge Carriersmentioning
confidence: 99%
“…Moreover, an extraordinarily high Kerr coefficient has been detected in a mixture of low-molar-mass NLC (5CB) and the azo dye C.I. Acid Red 2 [Methyl Red (MR) [14]]; this combination had attracted attention in the context of holographic gratings [15,16] including intensity gratings [17]. It has been demonstrated that a small amount of dye (w1%) dissolved in NLC enhances the reorientation of the NLC molecules by almost two orders of magnitude [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These two types of polarization holography have been applied to other photosensitive materials to create patterned alignment regions in azobenzenes, 22 dye-doped liquid crystals, 23 polymer liquid crystals, 24 and polymer-dispersed liquid crystals. [25][26][27] In our situation, the continuously varying polarization "imprint" on the alignment layers is most useful for aligning liquid crystal ͓Fig. 1͑c͔͒.…”
Section: Phase Holographymentioning
confidence: 99%